EDUCATIONAL INEQUALITY THROUGH A NUMBER OF STUDIES - Quy, Truong Thi Thanh (IJRDO- Journal of Educational Research, 2018)
“Everyone has the right to education. Education must be free, at least in elementary and middle school. Primary education must be compulsory, technical and vocational education must be accessible to everyone, and higher education must follow the principle of equality for all who are capable”. To enjoy education is the "natural right" of each person, especially children. But in fact, studies in the world show that many people and many children do not enjoy that natural right. They are experiencing inequalities in education (illiteracy) - the cause of inequality and other inequities in society such as poverty, ill health, disease ...